The effect of public tax service and Value Added Tax (VAT) rate increase on tax compliance with patriotism as a moderating factor - Murtanto, Murtanto; Situmorang, Septy Ananda (WIM Solusi Prima, 2025)
This study aims to examine the impact of Public Tax Service on taxation and the effect of the Value Added Tax (VAT) rate increase on the compliance of Micro, Small, and Medium Enterprises (MSMEs) taxpayers registered at the Jakarta Tebet Primary Tax Office. The planned VAT rate adjustment in 2025 is anticipated to significantly affect tax compliance. Since the VAT rate increased to 11% in 2022, it has posed substantial challenges, particularly in terms of rising production costs and reduced consumer purchasing power. This has prompted researchers to investigate the potential impact of a further VAT rate increase to 12%, in relation to the public tax services provided and its influence on the tax compliance of MSME taxpayers. This study utilizes primary data collected through direct surveys using questionnaires distributed to individual taxpayer respondents via Google Forms. The research employs multiple linear regression analysis using SPSS version 24 for data processing. The results indicate that the variable of Public Tax Service, when moderated by patriotism, does not significantly affect tax compliance. However, the VAT rate increase, together with patriotism as a moderating factor, collectively influences taxpayer compliance. This study utilizes primary data collected through direct surveys using questionnaires distributed to individual taxpayer respondents via Google Forms. The research employs multiple linear regression analysis using SPSS version 24 for data processing. The results indicate that the variable of Public Tax Service, when moderated by patriotism, does not significantly affect tax compliance. However, the VAT rate increase, together with patriotism as a moderating factor, collectively influences taxpayer compliance. Keywords: VAT rate increase, tax compliance, patriotism, tax public service